PEMANTAUAN TERAPI OBAT PADA PASIEN DEMAM TIFOID DI RUANG PERAWATAN ANGGREK308 DI RUMAH SAKIT dr. SUYOTO PUSREHAB KEMHAN Jl. RC. Veteran No. 178 Bintaro-Jakarta Selatan Periode 2 Mei – 21 Juni 2017 - Munarsih, Fetri Charya (Universitas 17 Agustus 1945 Jakarta, 2017)
Given the high sufferers of typhoid fever suffered by the community, especially in Indonesia.So that the role of Pharmacist is needed in the pharmacy service in the Hospital, therefore in the Pharmacist Profession Practice (PKPA) is performed monitoring patient treatment or study of cases of typhoid fever taken from the orphanage treatment unit at the inpatient Installation dr. Suyoto Hospital Pusrehab Kemhan Jakarta.Patient with the name Mrs. VVR,of 29-year-old entered the emergency room (observation) on May 1, 2017 and entered in the inpatient room (Orchid 308) on May 1, 2017 Patients diagnosed with Typhoid Fever with complaints Clients declared fever up and down H - 3, nausea, diarrhea 5 times, last afternoon, mouth bitter, lack of appetite, headache while sitting, pee no blood.Patients receiving treatment include Oral Sanmol, Oral Lactulax, Oral Fg Troches, Oral Hepabalance, Ondansetron Injection, Omeprazole Injection, Cefotaxime Injection, and Cefixime orally. Based on the analysis of therapeutic therapy it can be concluded that some of the drugs given to the patient in accordance with the indication, complaints and medical supporting data as well as the diagnosis are still rational, but the giving of some drugs must be paid for their use before they are given to the patient, monitored and regulated by drug interactions such as Fg Troches with Cefotaxime, Fg Troches with Cefixime and Fg Troches with Omeprazol.